Zygosaccharomyces bailii Is a Potential Producer of Various Flavor Compounds in Chinese Maotai-Flavor Liquor Fermentation - Xu, Yan; Zhi, Yan; Wu, Qun; Du, Rubing; Xu, Yan (Frontiers in Microbiology, 2017)
Zygosaccharomyces bailii is a common yeast in various food fermentations. Understanding the metabolic properties and genetic mechanisms of Z. bailii is important for its industrial applications. Fermentation characteristics of Z. bailii MT15 from Chinese Maotai-flavor liquor fermentation were studied. Z. bailii MT15 produced various flavor compounds, including 19 alcohols, six acids, three esters, three ketones, and two aldehydes. Moreover, production of acids and aldehydes were increased by 110% and 41%, respectively, at 37 oC (the maximum temperature in liquor fermentation) compared with that at 30 oC, indicating its excellent flavor productivity. Z. bailii MT15 is a diploid with genome size of 20.19 Mb. Comparative transcriptome analysis revealed that 12 genes related to amino acid transport were significantly up-regulated (2.41- to 5.11-fold) at 37 oC. Moreover, genes ARO8, ARO9, and ALDH4 involved in amino acid metabolism also showed higher expression levels (> 1.71-fold) at 37 oC. Increased substrate supply and a vigorous metabolism might be beneficial for the increased production of acids and aldehydes at 37 oC. This work revealed the potential contribution of Z. bailii to various flavor compounds in food fermentation, and produced insights into the metabolic mechanisms of Z. bailii in flavor production.